Analisis Vegetasi Tumbuhan Bawah Metode Garis Menyinggung Di Hutan Pendidikan Gunung Walat - Firman Ali Rahman Ali; Taufik Arianto; Masyarani Sulaiman; Yuliantin; Sulistijorini (Yayasan Tajuk Indonesia, 2024)
Gunung Walat Educational Forest is one of the ecosystems rich in biodiversity, including understory plants that play an important role in maintaining the ecological balance of the forest. This study aims to analyze understory vegetation in Gunung Walat Educational Forest using the line intercept method. This method was chosen because of its effectiveness in measuring the diversity, dominance, and distribution of understory plants in natural habitats. Data were collected by recording the types of plants that crossed the transect line, supplemented by measurements of density, frequency, and relative cover. The results showed that 16 types of understory plants were found in homogeneous and heterogeneous forest ecosystems including: Aghatis damara, Arenga undulatifora, Cinnanonum cintoc, Homalonema sp, Hornstedtia pinanga, Leea aquata indica, Melastoma malabathricum linn, Palmae, Pandanus furactum, Pinanna curunarri, Piper nigrum, Selaginella doederlinni, Shorea sp, Strubilentes crispus, Tetrastigma lanceolarium, and Zingiber zerumbe. The results showed that the number of understory plant species found in heterogeneous forests was higher than in homogeneous forests, with 17 and 15 species respectively. In homogeneous forests, the Selaginella doederleinii species dominates quantitatively with the highest relative density (46.26%), the highest relative frequency (39.70%), and the highest dominance (42.76%). This causes Selaginella doederleinii to have the highest important value index (INP) of 128.74%, followed by Tetrastigma lanceolarium (68.62%) and Homalonema sp (17.92%). The biodiversity of homogeneous forests in GWUF shows a high species diversity index (H’), which is an average of 4.27 with a species evenness of 1.45.